Age and Technology Readiness Influences on Adults' Experiences with Highly Automated Vehicles. Issue 6 (June 2023) - Mason, Justin; Classen, Sherrilene; Hwangbo, Seung Woo; Sisiopiku, Virginia P.
Adults' access to transportation may improve after the deployment of highly automated vehicles (HAVs). However, the public is hesitant to accept HAVs. This study investigated the influence of adults' ( n  = 210) age—younger (18–29 years), middle-aged (30–64 years), young-old (65–74 years), and older (>75 years)—and readiness to use technology on their intention to use, perceived barriers, well-being, and acceptance of HAVs before and after riding in an autonomous shuttle and a driving simulator operating in autonomous mode. Two-way mixed analysis of variances (ANOVAs) were deployed to assess changes between groups in Automated Vehicle User Perception Survey (AVUPS) domain scores after exposure to the HAVs. When controlling for baseline differences, well-being increased after exposure to HAVs for young-old adults compared with both middle-aged and younger adults. Both young-old and older adults reported greater intention to use compared with middle-aged adults. Regardless of age or technology readiness, adults' intention to use HAVs increased after experiencing the HAVs. Explorers displayed favorable perceptions (i.e., AVUPS domain scores) of HAVs whereas hesitators reported lower intention to use and acceptance of HAVs and more perceived barriers to adopting HAVs. The three other technology readiness classifications, skeptics, pioneers, and avoiders held relatively similar views of HAVs before and after exposure to both modes of HAVs. General beliefs about technology may inform automakers, autonomous mobility companies, human factors engineers, and driving rehabilitation scientists of adults' willingness to embrace emerging technology, especially when widespread exposure to the technology is not yet a reality.